Effect of different nitrogen levels and seed rates on growth, yield and quality of sorghum (Sorghum bicolor) fodder - AYUB, M; TANVEER, ASIF; ALI, SAFDAR; NADEEM, M ATHER (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted at FaisaJabad, Pakistan, during 1999 and 2000, to study the effect of 0, 60, 120 and 180 kg N/ha on 'JS 263' sorghum [Sorghum bicolor (L.) Moench]. and 80, 100 and 120 kg/ha seed ratesh. Nitrogen application significantly increased plant height, stem diameter, green fodder yield, leaf area, dry matter, crude protein, crude fibre and ash percentage. Increase in seed rate increased the plant height, green fodder yield and dry matter (%), but decreased ether extractable fat crude fibre, crude protein, ash, and leaf area significantly. Nitrogen levels of 120 and 180 kg/ha resulted statistically similar green fodder yield (59.38 and 59.67 tonnes/ha respectively). The seed rate of 120 kg/ha owing to higher stand density and plant height resulted in significantly higher green fodder yield (56.92 tonnes/ha) than 100 and 80 kg/ha. Both seed rate and nitrogen @ 120 kg/ha proved to be the best combination for getting higher green fodder yield of' JS 263' sorghum under Faisalabad conditions.